Access to affordable medicines after health reform: evidence from two cross-sectional surveys in Shaanxi Province, western China - Dr. Yu Fang, PhD; Anita K Wagner, DrPH; Shimin Yang, BS; Minghuan Jiang, MS; Fang Zhang, PhD; Dennis Ross-Degnan, ScD (Elsevier, 2013)
Background: Limited access to essential medicines is a global problem. Improving availability and affordability of essential medicines is a key objective of the National Essential Medicine Policy (NEMP) in China. In its initial implementation in 2009, the NEMP targeted primary hospitals with policies designed to increase availability of essential medicines and reduce patients' economic burden from purchasing medicines. We assessed medicine availability and price during the early years of the health reform in Shaanxi Province in underdeveloped western China. Methods: We undertook two public (hospitals) and private (pharmacy) sector surveys of prices and availability of medicines, in September, 2010 and April, 2012, by a standard methodology developed by WHO and Health Action International. We measured medicine availability in outlets at the time of the surveys and inflation-adjusted median unit prices (MUPs), taking 2010 as the base year. We used general estimating equations to calculate the significance of differences in availability from 2010 to 2012 and the Wilcoxon signed rank test to calculate the significance of differences in adjusted median prices. Findings: We collected data from 50 public sector hospitals and 36 private sector retail pharmacies in 2010 and 72 public hospitals and 72 retail pharmacies in 2012. Mean availability of surveyed medicines was low in both the public and private sectors; availability of many essential medicines decreased from 2010 to 2012, particularly in primary hospitals (from 27·4% to 22·3% for lowest priced generics; p<0·0001). The MUPs of originator brands and their generic equivalents decreased significantly from 2010 to 2012 in primary hospitals in comparison with secondary and tertiary hospitals. In the public sector, the median adjusted patient price was significantly lower in 2012 than in 2010 for 16 originator brands (difference −11·7%; p=0·0019) and 29 lowest-priced generics (-5·2%; p=0·0015); the median government procurement price for originator brands also decreased significantly (-10·9%; p=0·0004), whereas the decrease in median procurement price for lowest-priced generics was not significant (-4·9%; p=0·17). In the private sector, the median percentage decrease in price between 2010 and 2012 for 38 lowest-priced generics was 4·7% (IQR 6·3-13·2), compared with 7·9% (4·9-13·9) for 16 originator brands. Interpretation: Although inflation-adjusted medicine prices were numerically lower, there were concerning decreases in availability of lowest-priced generic medicines in both the public and private sectors in 2012 from already low availability in 2010. A long-term, stable, and consistent information system is needed to monitor effects of further implementation of the Chinese Essential Medicine Policy. Funding: The National Natural Science Fund (71103141/G0308), the China Medical Board Faculty Development Awards, the Fundamental Research Funds for the Central Universities (2011jdhz62), the Shaanxi Provincial Social Science Fund (10E066), and the Harvard Medical School Pharmaceutical Policy Research Fellowship.